The American Stamp Postal Iconography, Democratic Citizenship, and Consumerism in the United States - Goldblatt, Laura (Columbia University Press, 2023)
Examining the canon of nineteenth- and twentieth-century American stamps, Laura Goldblatt and Richard Handler show how postal iconography and material culture offer a window into the contested meanings and responsibilities of U.S. citizenship